Réticences françaises à l’égard des Postcolonial Studies : entre le soubresaut républicain et le hoquet francophone - Krzykawski, Michał (Romanica Silesiana)
The aim of this article is to analyze Francophony as a myth which is, according to Roland Barthes, “depoliticized speech” turning “the complexity of human acts” into “the simplicity of essences.” In Barthes’ way of approaching myth, I will try to demystify (demythologize) deep ideological structures of the Francophone discourse of universal and humanist values which seem to have never been reexamined in the francophone world so far. Now, if these values are similar to those preached by La République, which keeps believing that it has a monopoly on them, one can say that Francophony, whether we like it or not, is a political act. And that is not only in the sense of polis, as a community speaking the same language and recognizing the same values, but also in the sense of realpolitik, which needs to be understood as the continuation of an imperialistic gesture overshadowed by the neo-republican discourse of equality. Key words: Francophony, Myth, Mythologies, French Republic, Multiculturalism, French Theory.